Generation of Transgenic Mice that Conditionally Overexpress Tenascin-C - Yonebayashi, Saori; Tajiri, Kazuko; Hara, Mari; Saito, Hiromitsu; Suzuki, Noboru; Sakai, Satoshi; Kimura, Taizo; Sato, Akira; Sekimoto, Akiyo; Fujita, Satoshi; Okamoto, Ryuji; Schwartz, Robert J.; et al. (Frontiers in Immunology, 2021)
Tenascin-C (TNC) is an extracellular matrix glycoprotein that is expressed during embryogenesis. It is not expressed in normal adults, but is up-regulated under pathological conditions. Although TNC knockout mice do not show a distinct phenotype, analyses of disease models using TNC knockout mice combined with in vitro experiments revealed the diverse functions of TNC. Since high TNC levels often predict a poor prognosis in various clinical settings, we developed a transgenic mouse that overexpresses TNC through Cre recombinase-mediated activation. Genomic walking showed that the transgene was integrated into and truncated the Atp8a2 gene. While homozygous transgenic mice showed a severe neurological phenotype, heterozygous mice were viable, fertile, and did not exhibit any distinct abnormalities. Breeding hemizygous mice with Nkx2.5 promotor-Cre or -myosin heavy chain promoter Cre mice induced the heart-specific overexpression of TNC in embryos and adults. TNC-overexpressing mouse hearts did not have distinct histological or functional abnormalities. However, the expression of proinflammatory cytokines/chemokines was significantly up-regulated and mortality rates during the acute stage after myocardial infarction were significantly higher than those of the controls. Our novel transgenic mouse may be applied to investigations on the role of TNC overexpression in vivo in various tissue/organ pathologies using different Cre donors.